Tuberkuloza, naša ljudska, delavska in kmetska bolezen - Jaunig, Senta (Zgodovinski časopis, 2012)
Focusing on the prevention and control of tuberculosis, which until the 1960s represented among the Slovenes a serious societal problem, this paper addresses the interaction of medicine and the state. The prevalence of tuberculosis is conditioned by specific circumstances that are (or were) characteristic of early capitalist production. Its decline is likewise conditioned by changes within the production process. For almost half a century, tuberculosis was the first most common cause of death among the Slovenes. Since Slovenia was not a typical industrial country, the peak level of tuberculosis occurred at the turn of the 19th to the 20th century. In this period, developed countries already recorded its decline but in Slovenia, economic underdevelopment, poorly organized health organization, and the general lack of proper instruction and knowledge about the disease sustained the high incidence and mortality rate. In the politically turbulent times of the 20th century, the struggle to control tuberculosis received minimal support of the authorities prior to the Second World War. It was based mostly on charity and private initiative. However, after the war the state undertook a number of measurements to control the disease, and they have largely contributed to significantly reduce the number of tuberculosis cases.
Keywords: 19./20.st.; Antitubercular Agents; Antituberkulotiki; Dispanzerji; History; Javno zdravstvo; Mortality; Outpatient Clinics, Hospital; Political Systems; Politični sistemi; Prevention And Control; Public Health; Slovenci; Slovenes; Social Environment; Social Medicine; Socialna medicina; socialne bolezni; Socialno okolje; Tuberculosis; Tuberkuloza; zgodovinski pregledi